P53 codon 72 polymorphism and human papillomavirus associated skin cancer. Issue 7 (1st July 2001) - O'Connor, D P; Kay, E W; Leader, M; Atkins, G J; Murphy, G M; Mabruk, M J E M F
Abstract : Background/Aims —Non-melanoma skin cancers frequently harbour multiple human papillomavirus (HPV) types. A recent report suggests that a polymorphism of the p53 tumour suppressor gene that results in the substitution of a proline residue with an arginine residue at position 72 of the p53 protein might act as a risk factor in HPV associated malignancies. This study aimed to determine the following: (1) the relation between HPV infection and the development of cutaneous squamous cell carcinoma (SCC), and (2) whether there is a correlation between p53 codon 72 polymorphism and the development of SCC. Methods —Blood samples were taken from 55 patients with skin cancer (both renal transplant recipients and immunocompetent patients with skin cancer) and 115 ethnically matched volunteers. A polymerase chain reaction based assay was used to determine p53 codon 72 genotypes. In addition, 49 benign and malignant lesions from 34 of the patients with skin cancer and 20 normal human skin samples from 20 of the control volunteers were examined for HPV. Results —The proportions of p53 codon 72 genotypes found were 78% arginine homozygous, 2% proline homozygous, and 20% heterozygous among patients with skin cancer and 79% arginine homozygous, 3.5% proline homozygous, and 17.5% heterozygous among the control population. Statistical analysis showed no significant differences in the distribution of the two p53 isoforms between the patients with skin cancer and the control population. The predominant viral types detected in both the patients and the control group were EV associated HPVs, although the incidence was lower in normal skin samples than in malignant lesions or viral warts. Conclusions —These results suggest that in a Celtic population there is no correlation between the presence of HPV, the p53 codon 72 arginine polymorphism, and the development of skin cancer.